Pediatric intraoperative nerve monitoring during thyroid surgery: A review from the American Head and Neck Society Endocrine Surgery Section and the International Neural Monitoring Study Group. Issue 6 (8th March 2022) - Diercks, Gillian R.; Rastatter, Jeff C.; Kazahaya, Ken; Kamani, Dipti; Quintanilla‐Dieck, Lourdes; Shindo, Maisie L.; Hartnick, Christopher; Shin, Jennifer J.; Singer, Michael C.; Stack, Brendan C.; Chen, Amy Y.; St. John, Maie A.; et al.
Abstract: Children are more likely to experience recurrent laryngeal nerve (RLN) injury during thyroid surgery. Intraoperative nerve monitoring (IONM) may assist in nerve identification and surgical decision making. A literature review of pediatric IONM was performed and used to inform a monitoring technique guide and expert opinion statements. Pediatric IONM is achieved using a variety of methods. When age‐appropriate endotracheal tubes with integrated surface electrodes are not available, an alternative method should be used. Patient age and surgeon experience with laryngoscopy influence technique selection; four techniques are described in detail. Surgeons must be familiar with the nuances of monitoring technique and interpretation; opinion statements address optimizing this technology in children. Adult IONM guidelines may offer strategies for surgical decision making in children. In some cases, delay of second‐sided surgery may reduce bilateral RLN injury risk.